A cluster of conserved basic amino acids near the C-terminus of the PB1 subunit of the influenza virus RNA polymerase is involved in the regulation of viral transcription. - Kerry, P; Willsher, N; Fodor, E (2008)
Synthesis of influenza virus mRNA by the viral RNA polymerase complex is primed by capped RNA fragments generated by endonuclease cleavage of host pre-mRNA by the polymerase subunit PB1. In previous studies, endonuclease and promoter-binding sites have been described in the C-terminal region of PB1. Here, we have identified an additional region near the C-terminus of PB1 involved in producing capped RNA primers for viral transcription. In particular, mutations of basic amino acids K669, R670, and R672 inhibited primer-dependent viral mRNA synthesis. In contrast, primer-independent cRNA and vRNA syntheses were only marginally affected. Additionally, recombinant viruses containing the K669A or R672A mutations expressed reduced amounts of mRNA compared to cRNA during infection and were attenuated in cell culture. Further in vitro analysis showed that these mutations inhibited the ability of the polymerase to initiate mRNA synthesis by causing a reduction in binding to the vRNA promoter and capped RNA. These results suggest that this region plays a critical role in the regulation of viral mRNA transcription.